How Private and Public Debt Crises Exacerbate Housing Problems in the EU - Betavatzi, Eva; Toussaint, Eric (Κοινωνική Πολιτική, 2021)
The increase in mortgage lending in European countries since the 1990s’ is symptomatic of a political determination to push households into buying rather than renting on the housing market. Banks benefit from this as it allows them not only to increase their loan portfolios but also to use loans as securities and sell them on the secondary market. This results in credit bubbles which affect the global economy, as was the case in 2007-2008. Since then, in order to recapitalize their banks, many states have opted for public debt without imposing any substantial controls on the banking system and its ability to grant credit. Households have felt the effects of this in two ways: first, they have been confronted with a lack of affordable housing on the rental market, which has been left largely in the hands of the private sector and with little public investment or regulation; and second, austerity measures have caused their incomes to fall in order to pay off public debts. Thus, the increase in private and public debts, and the principle that they must be repaid whatever the cost, have an impact on the right to housing.